Circular RNA circHUWE1 Is Upregulated and Promotes Cell Proliferation, Migration and Invasion in Colorectal Cancer by Sponging miR-486 - Chen, Hong-Yu (Onco Targets Ther, 2020)
BACKGROUND: Emerging studies have revealed that circular RNAs (circRNAs) correlate with diverse diseases including cancers. However, little is known about the functions of circRNAs in colorectal cancer (CRC). In our previous research, downregulation of hsa_circ_0140388 (circHUEW1) has been detected in CRC tissues through high-throughput sequencing. However, the underlying mechanism by which circHUWE1 regulates the proliferation and apoptosis in CRC has not been investigated. MATERIALS AND METHODS: The levels of circHUWE1 in 58 pairs of CRC tissues and corresponding adjacent healthy tissues were detected by RT-qPCR. In addition, the effects of circHUWE1 on cell proliferation, apoptosis migration and invasion were evaluated by cell proliferation assays, flow cytometry, and transwell assays in HCT116 and SW480 cell lines respectively. Meanwhile, the dual-luciferase reporter system assay was used to explore the interaction between circHUWE1 and miR-486 (hsa-miR-486-5p). RESULTS: In this study, we demonstrate that the expression of circHUEW1 is upregulated in CRC tissues. High expression of circHUEW1 was significantly associated with lymphovascular invasion (P =0.036), lymph node metastasis (P =0.017), distant metastasis (P =0.024), and TNM stage (P =0.009). Moreover, the area under the curve (AUC) of the receiver operating characteristic (ROC) curve was 0.732, which indicated that circHUWE1 could serve as a potential biomarker in the detection of CRC. Silencing circHUWE1 significantly inhibited the proliferation, migration and invasion capacity of CRC cells in vitro. Mechanistically, we demonstrated that circHUWE1 could sponge miR-486 and the downregulation of miR-486 could reverse the cancer suppressive effects caused by silencing circHUWE1. CONCLUSION: In this study, our results revealed that circHUWE1 may be a potential therapeutic target and diagnostic biomarker for CRC.